ICT FACILITIES AND ACADEMIC LIBRARIES IN BRIDGING THE DIGITAL DIVIDE AMONG FACULTY MEMBERS - S.Esther Delsy; Dr.P. Thangavel (The Bioscan, 2026)
Information and Communication Technology (ICT) has become an essential part of higher education, supporting teaching, learning, and research. Academic libraries play an important role in bridging the digital divide by providing access to computers, the internet, digital resources, and technical support for faculty members. This study focuses on the role of ICT facilities and academic libraries in reducing digital inequalities among faculty members. It needs. The study aims to understand how academic libraries contribute to improving digital examines the availability and use of ICT facilities, digital library services, and library institutions.